Immunisation of Labeo rohita with Antigenic preparation of Aphanomyces invadans - Yadav, M. K.; Pradhan, P. K.; Sood, N.; Chaudhari, D. K.; Verma, D. K.; Chauhan, U. K.; Punia, P.; Jena, J. K. (Indian Journal of Fisheries, 2018)
Aphanomyces invadans is an important fungal pathogen infecting freshwater and brackishwater fishes. In the present study, an attempt has been made to determine the effect of immunisation in Labeo rohita advanced fingerlings against A. invadans infection. The efficacy of the immunisation was evaluated by challenge with A. invadans as well as quantification of antibody level by ELISA. Following an initial immunisation in conjunction with adjuvant, the fish were given a booster dose after 35 days. After 14 and 28 days of the booster injection, blood was collected from the immunised rohu for monitoring the antibody level. The fish were also challenged with A. invadans zoospores to determine the relative percent survival. The immunised fish had significantly higher antibody level after 14 days of booster injection as compared to the control fish. However, the antibody level after 28 days of booster injection was not significantly different from the control fish. More importantly, similar to control fish, 100% mortality was observed in the immunised fish challenged after 14 and 28 days of booster immunisation. Therefore, it can be concluded that it may not be suitable to induce protective immunity following immunisation with conventional antigenic preparations.